TEACHING AND LEARNING FRENCH AS A THIRD OR ADDITIONAL LANGUAGE IN AN INTERNATIONAL CONTEXT: SELECTED ASPECTS OF LANGUAGE AWARENESS AND ASSESSMENT - Włosowicz , Teresa Maria (Neofilolog, 2020)
The article investigates the teaching of French as a third or additional language (De Angelis, 2007) at the beginning level to international students from different language backgrounds and their learning of that language, as perceived by the students themselves, as well as revealed by tests. Special attention is paid to the areas of difficulty perceived by the students, their perception of the similarities and differences between French and their native languages as well as between French and other languages they already know, especially English, and of the teaching strategies, which included cross-linguistic awareness-raising. Assessment of their progress in French is also considered. The study involves a combination of two methods: long-term classroom observation and assessment of 29 students, and a questionnaire filled out by 20 of those students. As the results show, the participants’ awareness of similarities and differences is fairly high, but their attitudes towards awareness-raising, feedback, etc. vary considerably. The tests are both formative and summative (but also providing feedback). However, the feedback was mutual: apart from giving feedback to the students, the author could also modify her teaching according to their problems and wishes concerning the French classes.